2012
DOI: 10.1016/j.bbamcr.2011.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphorylation is a prerequisite for the Ca2+-dependent activation of Arabidopsis NADPH oxidases and may function as a trigger for the positive feedback regulation of Ca2+ and reactive oxygen species

Abstract: Reactive oxygen species (ROS) produced by NADPH oxidases play critical roles in signalling and development. Given the high toxicity of ROS, their production is tightly regulated. In Arabidopsis, respiratory burst oxidase homologue F (AtrbohF) encodes NADPH oxidase. Here we characterised the activation of AtRbohF using a heterologous expression system. AtRbohF exhibited ROS-producing activity that was synergistically activated by protein phosphorylation and Ca2+. The two EF-hand motifs of AtRbohF in the N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 39 publications
2
129
0
2
Order By: Relevance
“…Work performed in elicitor-treated suspension cultures indicated that phosphorylation and Ca 2+ signaling are required for ROS generation (Blume et al, 2000;Grant et al, 2000, Kimura et al, 2012, whereas other studies demonstrated that ROS production was necessary for Ca 2+ influx or played a positive feedback role (Van Breusegem et al, 2008). These studies revealed a specific and complex crosstalk between Ca 2+ and ROS signaling in early immune responses in different plant-pathogen interactions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Work performed in elicitor-treated suspension cultures indicated that phosphorylation and Ca 2+ signaling are required for ROS generation (Blume et al, 2000;Grant et al, 2000, Kimura et al, 2012, whereas other studies demonstrated that ROS production was necessary for Ca 2+ influx or played a positive feedback role (Van Breusegem et al, 2008). These studies revealed a specific and complex crosstalk between Ca 2+ and ROS signaling in early immune responses in different plant-pathogen interactions.…”
Section: Discussionmentioning
confidence: 89%
“…SOS1, a Na + / H + antiporter, which is a target of the SOS3/SOS2 complex, has been reported to be posttranscriptionally regulated by ROS and to interact with oxidative responses regulators (Katiyar-Agarwal et al, 2006;Chung et al, 2008). In rice cultured cells treated with PAMPs, CIPK14/15 appear to mediate ROS production (Kurusu et al, 2010), and, more recently, Arabidopsis CIPK26 was shown to interact with RBOHF in planta and positively and negatively regulate its ROS-producing activity in human cultured cells (HEK293T) (Kimura et al, 2012;Drerup et al, 2013). In planta validation of such results in the context of a specific physiological response will consolidate these promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpression of AtRbohD does not result in constitutive ROS production (Torres and Dangl, 2005), suggesting that Rboh may require posttranscriptional regulation for its activation. Arabidopsis RbohC/ RHD2, RbohD, and RbohF and rice RbohB are activated not only by Ca 2+ but also by protein phosphorylation (Ogasawara et al, 2008;Takeda et al, 2008;Kimura et al, 2012;Takahashi et al, 2012). And CDPK could activate the StRbohB protein through phosphorylation of the N-terminal region to regulate ROS production (Kobayashi et al, 2007).…”
Section: Ros Produced By Rboh Could Be Regulated By Ghcdpk1mentioning
confidence: 99%
“…1). Indeed, RBOHs are known to be modulated by Ca 2+ -dependent signaling both directly through their EF-hand motifs (Takeda et al, 2008;Kimura et al, 2012) and through posttranslational modulation, such as Ca 2+ -dependent protein kinase activity (e.g. Kimura et al, 2012;Drerup et al, 2013;Dubiella et al, 2013;Li et al, 2014;Monaghan et al, 2014).…”
Section: Ros Rbohs and The Calcium Wavementioning
confidence: 99%